A status quo analysis of disaster risk reduction policy and legislation in Cameroon. Issue 3 (30th May 2019) - Ashu, R.E.A.; Van Niekerk, Dewald
Abstract : Purpose: The purpose of this paper is to analyze the status quo of disaster risk reduction (DRR) policy and legislation in Cameroon. Design/methodology/approach: Using a qualitative method, this paper examines historical data from sectoral administrative reports, plans, declarations, commitments and speeches, texts and peer-reviewed journals on disaster and risk management in Cameroon for the period 1967-2017. Empirical data from ten selected government sectors were used to analyze the status quo, together with quantitative data collected by using four instruments (i.e. HFA Priority 1 & 4, USAID Toolkit, GOAL Resilience Score and the Checklist on Law and DRR). Findings: Findings show that Cameroon largely still practices disaster response through the Department of Civil Protection. Transparency and accountability are the sine qua non of the state, but the lack thereof causes improper implementation of DRR within development institutions. DRR is seen as an ad hoc activity, with the result that there is not effective institutional capacity for implementation. The need to develop a new national DRR framework is evident. Originality/value: Analyzing the status quo of DRR in Cameroon could assist with the review and reevaluation of a new DRR framework within the Cameroonian territory.